2003
DOI: 10.1007/s00234-002-0891-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse axonal injury: detection of changes in anisotropy of water diffusion by diffusion-weighted imaging

Abstract: Myelinated axons of white matter demonstrate prominent directional differences in water diffusion. We performed diffusion-weighted imaging on ten patients with head injury to explore the feasibility of using water diffusion anisotropy for quantitating diffuse axonal injury. We showed significant decrease in diffusion anisotropy indices in areas with or without signal abnormality on T2 and T2*-weighted images. We conclude that the water diffusion anisotropy index a potentially useful, sensitive and quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…Even though no large-scale DWI studies have been performed, a DWI study of 10 patients in the chronic phase showed increased mean ADC values in ROIs in the corpus callosum both in lesion and non-lesion areas. 14 The existing DTI studies addressing diffusivity in the corpus callosum in the chronic phase following TBI also support our findings. In a study of 30 TBI patients, higher MD was observed in the posterior corpus callosum at 12 months compared with healthy controls.…”
Section: Mean Adc Values and Comparison With Controlssupporting
confidence: 87%
See 1 more Smart Citation
“…Even though no large-scale DWI studies have been performed, a DWI study of 10 patients in the chronic phase showed increased mean ADC values in ROIs in the corpus callosum both in lesion and non-lesion areas. 14 The existing DTI studies addressing diffusivity in the corpus callosum in the chronic phase following TBI also support our findings. In a study of 30 TBI patients, higher MD was observed in the posterior corpus callosum at 12 months compared with healthy controls.…”
Section: Mean Adc Values and Comparison With Controlssupporting
confidence: 87%
“…[11][12][13] A DWI study of chronic TBI patients demonstrated increased mean ADC values in both visible lesions and normal-appearing tissue in the corpus callosum. 14 This finding corresponds to the increased MD observed in later DTI studies 5,15,16 and such changes in indices of diffusion are considered to reflect pathology in microstructure and architectural organization. 9 Some longitudinal studies have examined how changes in white matter diffusion properties evolve in the corpus callosum from the early to the chronic phase after TBI.…”
Section: Introductionsupporting
confidence: 59%
“…One measured diffusion anisotropy of the corpus callosum (splenium, body, genu) in 10 patients 2 weeks to 8 months after TBI (initial GCS scores ranged from 3 to 14) compared to normal individuals. 29 Diffusion anisotropy was decreased by an average of approximately 25% in at least one region of the corpus callosum in all 10 patients, indicating disruption of the normally highly ordered structure. Decreased anisotropy was found even in areas that looked normal on both FLAIR and GE images.…”
Section: Imaging Studiesmentioning
confidence: 87%
“…The TCI method is simple and objective and requires little cooperation from the patient; hence, this method has the advantage of excluding any cognitive impairment when the severity of the TBI was evaluated. To our knowledge, imaging was the only available technique that could evaluate the severity of DAI while the patient was alive [9,12,14]. Therefore, TCI may be a unique diagnostic tool for electrophysiologically evaluating the DAI by monitoring the CC lesions.…”
Section: Introductionmentioning
confidence: 99%